Amandla! Awethu!: Energy, Infrastructure, Rights, Services. Issue 6 (1st November 2016) - Wenzel, Jennifer
Abstract : This essay compares the role of energy infrastructures and electricity in social protest during and after the apartheid era in South Africa. The struggle against apartheid produced both a constitution unparalleled for its commitment to socioeconomic rights, and enduring visions of liberation that far exceed this legal framework. The varied new social movements and community protests that have sprung up in the past two decades amount to a post- (rather than anti-) apartheid struggle: a struggle against evictions and privatization, and for the realization of rights and the provision of basic infrastructural services. The tensions among rights, services and politics in contemporary South Africa lay bare some of the contradictions that make its history of racialized inequality so persistent in the present. The reprise of the 'Amandla! Awethu!' anti-apartheid slogan in the post-apartheid era is a suggestive example of a broader need to develop the critical and imaginative capacity to think, at a range of scales, between the two senses of power: what would it mean to bring 'power to the people'?